2013
DOI: 10.1149/2.077310jes
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Initial Reduction Temperature on the Microstructures and Performances of Ni/YSZ Anodes for Solid Oxide Fuel Cells

Abstract: This work focuses on the effects of the reducing and sintering behavior for NiO→Ni on the microstructures and performances of conventional Ni/YSZ (YSZ: yttria-stabilized zirconia) anodes for anode-supported solid oxide fuel cells (SOFCs). A strong dependence of reducing and sintering behavior on the initial reduction temperature for NiO→Ni was demonstrated. Some identical NiO/YSZ anodes were heated from room temperature (RT) to 850°C with a heating rate of 10°C/min. and the reducing gas H2 was provided at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…5), in contrast to the performance improvement that would be expected if NiO continued to reduce to Ni and improve electrode conductivity. The rapid NiO reduction has also been observed by other groups [32]. Thus, any structural changes responsible for degradation during 100 h testing are not primarily due to NiO reduction, and are instead attributed to the observed Ni particle agglomeration.…”
Section: Ni-ysz Degradation Mechanismssupporting
confidence: 75%
“…5), in contrast to the performance improvement that would be expected if NiO continued to reduce to Ni and improve electrode conductivity. The rapid NiO reduction has also been observed by other groups [32]. Thus, any structural changes responsible for degradation during 100 h testing are not primarily due to NiO reduction, and are instead attributed to the observed Ni particle agglomeration.…”
Section: Ni-ysz Degradation Mechanismssupporting
confidence: 75%
“…The solid volume reduction can be achieved by the formation of large amount of sub-micron inner pores. It has been reported that the reduction process at low temperature starts from the grain surface or boundary of NiO with relatively low binding energy [7,8,10], which explains the gaps formed at Ni-YSZ interface and inside Ni particle. During the temperature rise from 500 o C to 800 o C before operation, the closed pores coalesced and vanished due to Ni sintering as shown in Fig.…”
Section: -3mentioning
confidence: 99%
“…al. [10] have reported that the initial microstructure of Ni-YSZ and the corresponding anode performances can be controlled by reduction and sintering processes of NiO to Ni. A model was proposed to qualitatively describe the reducing and sintering mechanisms and combined effects on anode microstructure changes at different initial reduction temperatures.…”
mentioning
confidence: 99%
“…al. [18] have reported that the initial microstructure of Ni-YSZ and the corresponding performances can be influenced by the reducing and sintering processes of NiO to Ni. The reduction process starts from grain surface or grain boundary with relatively low binding energy.…”
Section: Introductionmentioning
confidence: 99%